Epidemiology of filamentous fungal infections in burned patients: A French retrospective study. Issue 4 (June 2015) - Schaal, J.V.; Leclerc, T.; Soler, C.; Donat, N.; Cirrode, A.; Jault, P.; Bargues, L.
Highlights Incidence of filamentous fungal infections (FFI) was 1.7%. FFI are essentially cutaneous and occur in the most severe burned patients. The patients do not present the classic immunosuppression risk factors. 30% of the patients with burn wound aspergillosis died. This series is the first one in Europe to describe burned patients with FFI.